Potato planter test bed based on capacitive precision seed-monitoring and miss-seeding compensation system - Zhang, Hua; Zhao, Wuyun; Sun, Wei; Wang, Guanping; Liu, Xiaolong; Feng, Bin; Shi, Linrong; Liu, Yan; Li, Hongling (International Journal of Agricultural and Biological Engineering, 2022)
Potato seed-monitoring is the premise of its precise planting. But, for anti-dust, anti-vibration performance and durability, the existing photoelectric monitoring schemes have obvious congenital defects. So, a capacitive precision seed-monitoring idea was proposed in this study. Its theoretical basis is that the variation of dielectric between the capacitor plates will inevitably induce the fluctuation of the detected capacitance value. Therefore, the construction of a space capacitance sensor, and the acquisition of the net capacitance fluctuation caused by the seed spoon passing through the space area of the capacitor plates, were the core focuses of this study. Firstly, the system theory and working principle was introduced. Next, a space capacitance sensor that meets all the requirements was analyzed and constructed. And then, its spatial arrangement was described in detail, and most important of all, the technology roadmap of the net capacitance fluctuation measurement were put forward. For this purpose, MAX038 and GD32F407 were selected to work together to measure the capacitance. From this way, the top value of the space capacitance when a spoon passed through the space capacitance sensor was detected, at the same time, the corresponding grating encoder information was also recorded, so, the net capacitance fluctuation of this process was calculated. Based on this result, normal-seeding, miss-seeding, and multi-seeding were identified. More subtly, with the cooperation of the grating encoder, the position of the seed-metering monitoring point was configured freely. Just for miss-seeding, a predictive impact compensation concept was suggested. Based on the theories above, the software core links related to seed-monitoring and compensation control were analyzed. Finally, a potato planter test bed based on this study was built. Taking the Long-7 cutting potato as test samples, it was found that, the capacitance measurement error was no higher than 0.6%; no misjudgment on miss-seeding was found, however, for normal-seeding and multi-seeding, there was a small amount of identification of the opposite kind was found, but not more than 1.0% and 1.5%, respectively. Because of the flexibility of the seed-metering monitoring point layout, the predictive impact compensation can also be arranged according to actual needs, and the mechanism of the impact compensation system is simple and direct, which makes it cheap and fast. Nevertheless, a lower compensating seed potato tank filling rate is conducive to the average compensation success rate at an acceptable level. This research has laid the engineering foundation for the industrial application of potato non-photoelectric seed-metering monitoring and miss-seeding compensation. Keywords: potato planter, capacitive precision seed-monitoring, space capacitance sensor, miss-seeding compensation system DOI: 10.25165/j.ijane.20221506.6785 Citation: Zhang H, Zhao W Y, Sun W, Wang G P, Liu X L, Feng B, et al. Potato planter test bed based on capacitive precision seed-monitoring and miss-seeding compensation system. Int J Agric & Biol Eng, 2022; 15(6): 104–112.